Recurrent transcriptional loss of the PCDH17 tumor suppressor in laryngeal squamous cell carcinoma is partially mediated by aberrant promoter DNA methylation. Issue 7 (6th April 2018) - Byzia, Ewa; Soloch, Natalia; Bodnar, Magdalena; Szaumkessel, Marcin; Kiwerska, Katarzyna; Kostrzewska‐Poczekaj, Magdalena; Jarmuz‐Szymczak, Malgorzata; Szylberg, Lukasz; Wierzbicka, Malgorzata; Bartochowska, Anna; Kalinowicz, Ewelina; Grenman, Reidar; et al.
Abstract : Protocadherins are cell‐cell adhesion molecules encoded by a large family of genes. Recent reports demonstrate recurrent silencing of protocadherin genes in tumors and provide strong arguments for their tumor supresor functionality. Loss of protocadherins may contribute to cancer development not only by altering cell‐cell adhesion, that is a hallmark of cancer, but also by enhancing proliferation and epithelial mesenchymal transition of cells via deregulation of the WNT signaling pathway. In this study we have further corroborated our previous findings on the involvement of PCDH17 in laryngeal squamous cell carcinoma (LSCC). We used bisulfite pyrosequencing to analyze a cohort of primary LSCC tumors for alterations in PCDH17 promoter DNA methylation as an alternative gene inactivation mechanism to the homozygous deletions reported earlier. Moreover, we analyzed primary LSCC samples by immunohistochemistry for PCDH17 protein loss. We identified recurrent elevation of PCDH17 promoter DNA methylation in 32/81 (40%) primary tumors ( P  < 0.001) and therein hypermethylation of 12 (15%) cases in contrast to no tumor controls ( n  = 24) that were all unmethylated. Importantly, DNA demethylation by decitabine has restored low level PCDH17 expression in LSCC cell lines. In conclusion, we provide a mechanistic explanation of recurrently observed PCDH17 silencing in LSCC by demonstrating the role of promoter methylation in this process. In light of these findings and recent reports showing that PCDH17 methylation is detectable in serum of cancer patients we suggest that testing PCDH17 DNA methylation might serve as a potential biomarker in LSCC.